Echo - Rex, Adam (Dial Books for Young Readers, an imprint of Penguin Random House, 2025)
"Everyone always agrees with Junior, including the mysterious voice from across the valley. 'Junior Junior is the greatest in the world!' he shouts. 'Junior Junior is the greatest in the world!' the echo shouts back. Until one day, a new girl moves in next door. A disagreeable, rude girl who doesn't think Junior is right all the time. Unable to stand living next door to someone like that, Junior runs to the valley to meet his echo. But when being around someone who agrees with him all the time is less fun than he imagines, Junior must decide if a new friend is worth admitting he was wrong"--